Navigating redox imbalance: the role of oxidative stress in embryonic development and long-term health outcomes - Divvela, Satya Srirama Karthik; Gallorini, Marialucia; Gellisch, Morris; Patel, Gaurav Deepak; Saso, Luciano; Brand-Saberi, Beate (Frontiers in Cell and Developmental Biology, 2025)
Embryonic development is a complex process of concurrent events comprising cell proliferation, differentiation, morphogenesis, migration, and tissue remodeling. To cope with the demands arising from these developmental processes, cells increase their nutrient uptake, which subsequently increases their metabolic activity. Mitochondria play a key role in the maintenance of metabolism and production of reactive oxygen species (ROS) as a natural byproduct. Regulation of ROS by antioxidants is critical and tightly regulated during embryonic development, as dysregulation results in oxidative stress that damages essential cellular components such as DNA, proteins, and lipids, which are crucial for cellular maintenance and in extension development. However, during development, exposure to certain exogenous factors or damage to cellular components can result in an imbalance between ROS production and its neutralization by antioxidants, leading to detrimental effects on the developmental process. In this review article, we highlight the crucial role of redox homeostasis in normal development and how disruptions in redox balance may result in developmental defects.